Volume 1B: General 1970
DOI: 10.1115/70-gt-105
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Ceramics to the Small Gas Turbine

Abstract: This paper reviews the limitations today’s superalloys exercise on the realization of the potential of the gas turbine engine. Ceramic materials are suggested as a means of achieving lower cost and higher turbine inlet temperature in small gas turbine engines. The paper serves to introduce ceramic materials and processing techniques and identifies silicon nitride, silicon carbide and lithium-alumina-silicate as promising materials for high temperature turbine engine components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Over 15 years ago, a British attempt to use ceramics, notably silicon carbide, for the nozzle vanes of an industrial gas turbine was reported by Blakely (l),l although this work has not, perhaps, received the publicity it deserved. Much more recently, progress in the development of ceramics for vehicular gas turbines has been reported by McClean (2). Since this publication, substantial research work has been carried out on determining the mechanical properties of representative ceramics, and many papers have been presented on applications for vehicular and industrial gas turbines.…”
Section: Gas Turbine Advancementsmentioning
confidence: 99%
“…Over 15 years ago, a British attempt to use ceramics, notably silicon carbide, for the nozzle vanes of an industrial gas turbine was reported by Blakely (l),l although this work has not, perhaps, received the publicity it deserved. Much more recently, progress in the development of ceramics for vehicular gas turbines has been reported by McClean (2). Since this publication, substantial research work has been carried out on determining the mechanical properties of representative ceramics, and many papers have been presented on applications for vehicular and industrial gas turbines.…”
Section: Gas Turbine Advancementsmentioning
confidence: 99%
“…On the other hand, developments of reaction sintered silicon nitride showed that injection molded, Type C, material with low calcium levels, had low creep characteristics, also shown in Table 1. Further studies of reaction sintered silicon nitride made by slip casting and coded NE 10, showed 2 Faced with the lack of success in making a one-piece rotor from hot pressed silicon nitride, a new approach was conceived called a "duo-density silicon nitride rotor." In this, as shown in Fig.…”
Section: Hot Gas Flowmentioning
confidence: 99%
“…The potential benefits in using ceramics (2) are improved engine efficiency and size by operating at higher turbine inlet temperature, and lower cost by using materials more readily available and abundant than conventional turbine superalloys. For example, an increase in turbine inlet temperature from 986 C with today's uncooled superalloys to 1371 C with ceramics would result in a doubling of horsepower for the same size engine and a 20-30 percent improvement in efficiency at full power; even greater efficiency gains would be realized at less-than-full-power, which is especially significant for automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few materials are available that possess both the thermal and mechanical stress capabilities and the corrosion-erosion resistance required by uncooled nozzle guide vanes operating at turbine inlet temperatures of 2500 F. The silicon compounds are especially promising. Of these, SiC and Si3N4 are the most frequently recommended for gas turbine application (1)(2)(3). Screening tests at Westinghouse established that both Si3N4 and SiC are leading candidate materials for industrial gas turbine application when they are fabricated as fully dense, high-strength ceramics.…”
Section: Materials Requirementsmentioning
confidence: 99%
“…Progress in the development of a ceramic vehicular turbine at Ford Motor Company was recently reviewed by A. F. McLean (1). 1 A case for the use of ceramics in industrial gas turbine will be discussed in the present paper.…”
Section: Introductionmentioning
confidence: 99%